Screening young athletes for prevention of sudden cardiac death: Practical recommendations for sports physicians - Chatard, J.-C.; Mujika, I.; Goiriena, J. J.; Carre, F. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Regular intensive exercise in athletes increases the relative risk of sudden cardiac death (SCD) compared with the relatively sedentary population. Most cases of SCD are due to silent cardiovascular diseases, and pre-participation screening of athletes at risk of SCD is thus of major importance. However, medical guidelines and recommendations differ widely between countries. In Italy, the National Health System recommends pre-participation screening for all competitive athletes including personal and family history, a physical examination, and a resting 12-lead electrocardiogram (ECG). In the United States, the American College of Cardiology and the American Heart Association recommend a pre-participation screening program limited to the use of specific questionnaires and a clinical examination. The value of a 12-lead ECG is debated based on issues surrounding cost-efficiency and feasibility. The aim of this review was to focus on (i) the incidence rate of cardiac diseases in relation to SCD; (ii) the value of conducting a questionnaire and a physical examination; (iii) the value of a 12-lead resting ECG; (iv) the importance of other cardiac evaluations in the prevention of SCD; and (v) the best practice for pre-participation screening.